Scaling up organic agricultural enterprises: An empirical study of the role of associations of micro producers - Jasmina Božić (Business Systems Research (BSR), 2024)
Background Development of organic agricultural entrepreneurship often requires "scaling up" from a multitude of individual, largely disconnected micro organic enterprises with haphazard achievements, toward more integrated units, operating more systematically and allowing for replication of their achievements on a larger territorial and temporal scale. Objectives The current states of activity, sectoral and inter-sectoral cooperation of Croatian associations of micro organic producers are assessed with a view to instigate and facilitate scaling up processes. Methods/Approach The inquiry is based on thematic analysis of qualitative data collected through semi-structured interviews with representatives of Croatian associations of micro organic producers. Results Lessening of tension between farmers' strivings for autonomy and their need for mutual cooperation, trust in interpersonal relationships and organizational structures, and integration through value-based supply chains (VBSCs) are identified as important aspects of scaling-up. Conclusions Scaling-up processes are distinctly path-dependent and, although examples of earlier working practices are welcome, they can seldom be carbon copied in different developmental contexts. Conceptualization of scaling up as intensification of relational interdependencies among various organizational units at several levels of aggregation underlines the need for strengthening the role of associations of micro producers as intermediaries between family farms and other, more complex, inter-sectoral organizational forms.
Keywords: L31; L38; Q01; Q18; 330; ecological food production; micro entrepreneurship; neoendogenous development; organic farming; rural development; scaling up